HYDRO POWER SCENARIO IN INDIA - Rajib Chakraborty (International Journal of Innovations in Engineering Research and Technology, 2021)
Though Indian civilisation emerged in the Indus valley in 3300 BCE with urban ideas, India’s first introduction to electricity was on 15th January 1897, in Calcutta under British Rule. After independence a stress was given to generate more hydropower for a period of about 20 years. But due to various reasons the stress on hydro power gradually reduced and thermal power got more focused. The present Hydro thermal ratio in India is 23:77. In spite of having a hydropower potential of 250000 MW (including storage pump schemes) till date India has harnessed only 20 % of the potential. Presently India ranks 5th in generation of Hydro power in the world. In 2003 after reforming the policies in National Electricity Plan, Indian government was trying to boost hydropower by identifying and distributing 162 projects of hydro capacity of 47,930 MW mostly to Private developers. Despite government efforts, issues like environmental clearances, less geotechnical investigations, R&R problems, land acquisition issues, interstate disputes, finance initiative have influenced the development of hydro power generation, with a slippage of 9,500 MW in the 11th Plan and the optimistic target of the 12th Plan. After that a realistic plan has been taken in 12th and 13th Plan. In the recent Pasis Climet Agreement India has taken a target of 40 per cent non-fossil-based power capacity by 2030. To achieve this augmentation of hydropower and with solar and wind power in inevitable. Solar and wind are intermittent sources of power and to ensure an efficient and stable grid we need sources to respond to the fluctuations. Hydro with its inherent capabilities to quickly ramp up or swiftly shut off the generation is a critical . India will take a target to double is hydro power resources by next decade